RELEVANSI KEMAMPUAN ALUMNI PROGRAM STUDI TEKNIK SIPIL TERHADAP DUNIA KERJA - Mahdi Mahdi (Jurnal Optimalisasi, 2016)
Competitive world of construction to create quality jobs in accordance with the wishes of the people are increasingly high, not only large contractors are trying as much as possible, medium and even small contractors will strive to improve the quality of work in accordance with the wishes of the people. This study aims to determine how relevant competence factors include knowledge, skills, and attitudes gained from the lectures of Civil Engineering University Almuslim with the needs in the world of work as well as knowing the difference of perception based on the role of the respondents (contractors and consultants) and work experience of respondents (under 4 year, 4 to 8 years, over 8 years). This research was conducted by distributing a questionnaire addressed to alumni of the University of Civil Engineering Program Almuslim that work to contractors and consultants who are directly involved in a construction project. Furthermore, all kuesoiner which were collected and analyzed statistically using the analysis Independent Sample T-test, and one way Analysis of Variance (ANOVA) using SPSS. From the analysis we found that the factor most relevant competences between the educational curriculum of Civil Engineering University Almuslim with the needs of the workforce total is "Reinforcement and Expenses Detail Bending, Axial, Slide, and Torque" on knowledge. For the skill aspect, the greatest subvariable is "Being able to become independent learners follow the development of science in civil engineering". For the aspects of attitude, the highest subvariable is "Experience". In addition, from the results of the analysis showed that there was no difference of perception based on the role and experience of the respondents.Keywords: Relevance, Capabilities, Competencies.